Occurrence of Toxic Substances Inhibiting the Nitrification in Waste Water from Industrial Zones in Vietnam - Friedrichs, Ferdinand; Rudolph3, Karl Ulrich; Panning4, Frank; Huyen, Pham Thi; Genthe, Wolfgang; Trung, Do Quang (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: By using a mobile laboratory with toxicity as a key parameter, the occurrence of toxic wastewater in two Vietnamese industrial zones and one factory was investigated. During this measurement campaign in two industrial zones a monitoring of the centralized wastewater treatment plants (WWTP) and the sewage systems of the industrial zones was carried out. Furthermore, the influent and effluent of a chemical WWTP at the company Groz-Beckert was investigated, to assess the removal of heavy metals by the chemical treatment. The toxicity screening showed that nitrification inhibiting substances occurred in the two investigated industrial zones. A centralized WWTP in a North Vietnamese industrial zone Nam Sach showed toxicities up to 60% in the wastewater treatment plant’s effluent. These toxic substances inhibited the biological degradation of organic pollutants by the activated sludge bacteria for three days. The online toxicity monitoring of the centralized WWTP in the Hoa Cam industrial zone inCentral Vietnamshowed shock dosing of nitrification inhibiting substances in effluent with toxicities up to 50%. The toxicity monitoring of the chemical WWTP at the factory of company Groz-Beckert proved that the heavy metal removal was done successfully, these results were confirmed with ICP measurements. Keywords: Monitoring, toxicity, nitrification inhibition, industrial wastewater, online measurements.